2022
DOI: 10.1002/inf2.12320
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive, flexible perovskite nanowire photodetectors with long‐term stability exceeding 5000 h

Abstract: Photodetectors (PDs) based on perovskite nanowires are among the most promising next‐generation photodetection technologies; however, their poor long‐term stability is the biggest challenge limiting their commercial application. Herein, an ionic liquid, 1‐butyl‐3‐methylimidazolium tetrafluoroborate (BMIMBF4), is incorporated as an additive into methylammonium lead triiodide (MAPbI3) nanowires; this not only effectively passivates defects to inhibit perovskite degradation but also leads to the formation of nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 58 publications
0
54
0
Order By: Relevance
“…The EQE (external quantum efficiency) spectrum of the Pt–Ag photodetector was recorded at 0 V (Fig. S6b, ESI † ), R is a function of EQE, which is calculated by the following formula: 57 where h , c , and q are Planck constant, the velocity of light, and the unit charge, respectively. The EQE value for the photoresponse is 26.74% at 530 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The EQE (external quantum efficiency) spectrum of the Pt–Ag photodetector was recorded at 0 V (Fig. S6b, ESI † ), R is a function of EQE, which is calculated by the following formula: 57 where h , c , and q are Planck constant, the velocity of light, and the unit charge, respectively. The EQE value for the photoresponse is 26.74% at 530 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Adding 1-butyl-3-methylimidazolium tetrafluoroborate (BMIMBF4) as an additive to MAPbI 3 NWs improved device performance owing to fewer defects, better crystallization, enhanced light absorption, and improved charge transfer in MAPbI 3 NWs. The NW PD exhibited remarkable performance with a detectivity, linear detection range, and noise-equivalent power of 2.06 × 10 13 Jones, 160 dB, and 1.38 × 10 −15 W Hz −1/2 , respectively, and the stability of the device was effectively improved [ 107 ].…”
Section: Application Of Perovskite Nanowiresmentioning
confidence: 99%
“…In comparison with polycrystalline thin films, perovskite single crystals (SCs) have superior low trap density, 31 long diffusion length, 32 high carrier mobility and especially high stability, 68,71,72 which makes them attract much attention in photoelectric detection. [33][34][35] Zou et al reported a perovskite SC/ graphene vertical structure with high photodetectivity (B2 Â 10 13 Jones).…”
Section: Introductionmentioning
confidence: 99%